Hate Spin : The Manufacture of Religious Offense and Its Threat to Democracy - George, Cherian (Book collections on Project MUSE., 2017)
Eruptions of religious intolerance are often described as spontaneous and visceral. This work, however, argues that most major episodes of religious offense are purposefully manufactured by political entrepreneurs.